Dinamika Kepribadian Tokoh dalam Novel Konspirasi Alam Semesta Karya Fiersa Besari - Annisa, Resmita Nadlofa Rizqi; Israhayu, Eko Sri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Humans are created with two types of inherent personalities, namely positive and negative personalities. The attitude or personality that exists in each individual can change due to events that have occurred in the past, and differences in personality possessed by individuals can also cause conflicts that lead to anxiety. This is what is called the dynamics of personality which can also be contained in the novel which contains the author's way of expressing an event through his fictional characters. This study aims to describe the personality dynamics that occur in the characters in the novel Conspiracy of the Universe by Fiersa Besari. This type of research includes qualitative descriptive research with a literary psychology approach. The data in this study are in the form of whole sentences or quotes that reflect the personality or behavior of the characters who are included in the personality dynamics which are divided into instincts and anxiety in Fiersa Besari's novel Conspiracy of the Universe by Fiersa Besari. The data collection technique uses reading techniques and note-taking techniques. Data analysis used techniques with three steps, namely data reduction, data presentation, and drawing conclusions or verification. The results of this study reveal that the dynamics of personality found in the characters Juang Astrajingga and Ana Tidae are instincts and anxiety which include 6 data on life instincts in the form of sex instincts, thirst, creative activities and instinctive derivatives. Furthermore, 2 data on death instinct in the form of aggressive verbal and non-verbal activities, 6 data on realistic anxiety, 1 data on neurotic anxiety, and 1 data on moral anxiety. Keywords: novel, character, personality dynamics, literary psychology, psychoanalysis